Exploring the association between sexual motivation and quality of life in China and the United Kingdom. - Shijun Zheng; Heather L Armstrong (PLoS ONE, 2023)
Previous research suggests that different sexual motivations may be associated with different sexual behaviours and levels of sexual satisfaction, and these may vary with cultural differences. As such, sexual motivations and cultural factors might also be associated with quality of life (QoL); however, this has not yet been explored. Using a biopsychosocial approach, this study aimed to explore associations between sexual motivation and quality of life between participants in the United Kingdom and China. 276 participants (143 British, 133 Chinese, mean age = 21.5 years) completed an anonymous online survey including validated measures for sexual motivation (YSEX?-SF) and QoL (WHOQOL-BREF). In multivariable linear regressions, pleasure motivations for sex were associated with increased physical health QoL (aOR = 0.20, 95%CI:.15-.65), while love and commitment motivations were associated with increased psychological health QoL (aOR = 0.13, 95%CI:.01-.43). Both love and commitment motivations (aOR = 0.21, 95%CI:.09-.35) and pleasure motivations (aOR = 0.20, 95%CI:.08-.36) were associated with increased social support QoL. A significant interaction was found between emotional motivations and culture (p = 0.037) such that among individuals from China, emotional motivations (i.e., love and commitment and expression) were positively associated with psychological QoL. This suggests culture may differentially affect how sexual motivations are associated with QoL and warrants further consideration in future research.